Biomechanical analysis of the waterpolo fast shot: centre of gravity movement - Ball, K. (Proceedings of the First Australasian Biomechanics Conference, 1996, Sydney, 1996)
The purpose of this study was to assess a technique for quantifying full body mechanics in the water environment and compare good and poor performers during a shot for maximal speed (termed 'fast shot' for this study) in terms of ball speed and COG movement. Results: To assess the accuracy of combining above and below water views, the two cubes of different dimensions were digitised and reconstructed. Errors of less than one percent existed in this reconstructed cube data, which was considered acceptable for this study. The cubes maintained dimensions and angles. There was a significant difference in ball velocity between group 1 (21.87m/s) and group 2 (18.95m/s). Lateral movement velocity at release (Z axis) was significantly different between groups. Group 1 exhibited greater velocity at release (0.777m/s) compared to group 2 (0.406m/s) . Although only significant at p<0.06, the displacement of the COG during forward swing in the Z axis was also larger for group 1 (0.128m) than for group 2 (0.096m). (from: Proceedings of the First Australasian Biomechanics Conference; ISBN 0 86758 999 X)